AB0995 Protein Losing Enteropathy (PLE) in a Child: The First Clinical Presentation of Systemic Lupus Erythematosus-Like Syndrome?. (9th June 2015) - Fontana, F.; Timpone, L.; Aloy, G.; Orlando, F.; Alessio, M.
Abstract : Background: PLE has been seldom associated to SLE. Even more rarely, PLE has been described in infancy, as initial and unique clinical presentation of SLE. Methods: Clinical case: VM an adopted 10-year-old Vietnamese child, was first admitted to a hospital for sudden generalized oedema at 8 years of age. On admission, hypoalbuminaemia, hypocomplementaemia and a 24-h urinary protein quantification of 610 mg were noticed. For a nephrotic syndrome suspicion, he received daily oral prednisone for 1 month, followed by 4 months of steroid tapering, with complete recovery. One year later, he was again admitted to a hospital for sudden generalized oedema. Laboratory studies showed hypoalbuminaemia, hypocomplementaemia and a 24-h urinary protein quantification of 346 mg. ANAs and dsDNA antibodies were highly positive; serum IgG were elevated too. Because of the suspicion of a nephrotic syndrome relapse, he received a new course of daily oral prednisone for 3 months, followed again by a complete normalization of albumin blood values. After a prednisone free period of 9 months, the patient was admitted to our unit for a third episode of sudden generalized oedema. At clinical examination a conspicuous limbs and periorbital oedema was present. The blood albumin was so low to be undetectable. Again, liver and kidney function were normal, such as 24-h urinary protein. ANAs were positive with speckled appearance, while dsDNA antibodies were absent. Complement was normal. Fecal alpha-1 antitrypsin was of 7.21 mg/g (normal range 0.38-0.5). The Tc-labelled human serum albumin scintigraphy confirmed a severe PLE, mostly deriving from the duodenojejunal area. Gastrointestinal endoscopies showed gastric hypertrophic folds with mucosal nodularity, and lymphoid nodular hyperplasia to the distal ileum. Biopsies revealed a gastric mucosal chronic inflammation with foveolar hyperplasia and microscopic lymphangiectasias. The patient was first started to a nutritional replacement using high-protein diet and medium-chain triglycerides, without a significant improvement of serum albumin. The diagnosis of LUPLE (LUpus Protein Losing Enteropathy) was suspected. Treatment with alternate days i.v. methylprednisolone (20 mg/kg/day) was commenced, followed after one week by daily oral prednisone (1 mg/kg/day) combined to daily oral azathioprine (2 mg/kg/day), with a progressive improvement in albumin blood values. Conclusions: PLE is a rare manifestation of autoimmune diseases, including SLE, but the underlying autoimmune disorder is not necessarily apparent at the time of onset of PLE. This case highlights the need of considering PLE as possible etiology of acute hypoalbuminaemia in apparently otherwise healthy children, even without any gastrointestinal symptom. In addition, it is a rare example of PLE as initial and unique clinical presentation of an autoimmune process in childhood. References: Al-Mogairen SM. Lupus protein-losing enteropathy (LUPLE): a systematic review. Rheumatol Int 2011;31:995-1001. Awazawa R, Yamamoto Y, Mine Y et al. Systemic lupus erythematosus complicated with protein-losing enteropathy: a case report and review of the published works. J Dermatol 2012;39:454-61. Disclosure of Interest: None declared